Stratigraphycal and petrographycal aspects of jurassic volcanism of the peruvian south coast (departments of Moquegua and Tacna) - Alejandro, V. (2006)
Petrographycal aspects of jurassic volcanic deposits of the Peruvian south coast are analyzed in the present work, which correspond to andesites and basalts corresponding to the Chocolate Formation and Chert stratified facies of the Guaneros Formation, the volcanic ones belong to a system of volcanic arc whereas deposits of the Guaneros Formation are signal of a cortical thinning for this period in the Peruvian South margin.